Mitochondria regulate MR1 protein expression and produce self-metabolites that activate MR1-restricted T cells - Gennaro Prota; Giuliano Berloffa; Wael Awad; Alessandro Vacchini; Andrew Chancellor; Verena Schaefer; Daniel Constantin; Dene R. Littler; Rodrigo Colombo; Vladimir Nosi; Lucia Mori; Jamie Rossjohn; et al. (Proceedings of the National Academy of Sciences, 2025)
Mitochondria coordinate several metabolic pathways, producing metabolites that influence the immune response in various ways. It remains unclear whether mitochondria impact antigen presentation by the MHC-class-I-related antigen-presenting molecule, MR1, which presents small molecules to MR1-restricted T-lymphocytes. Here, we demonstrate that mitochondrial complex III and the enzyme dihydroorotate dehydrogenase are essential for the cell-surface expression of MR1 and for generating uridine- and thymidine-related compounds that bind to MR1 and are produced upon oxidation by reactive oxygen species. One mitochondria-derived immunogenic formylated metabolite we identified is 5-formyl-deoxyuridine (5-FdU). Structural studies indicate that 5-FdU binds in the A’-antigen-binding pocket of MR1, positioning the deoxyribose toward the surface of MR1 for TCR interaction. 5-FdU stimulates specific T cells and detects circulating T cells when loaded onto MR1-tetramers. 5-FdU-reactive cells resemble adaptive T cells and express the phenotypes of naïve, memory, and effector cells, indicating prior in vivo stimulation. These findings suggest that mitochondria may play a role in MR1-mediated immune surveillance.